2019
DOI: 10.35808/ersj/1432
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Social Responsibility on Customer Trust and Brand Equity: An Evidence from Social Commerce in Thailand

Abstract: Purpose:The purpose of this study is to investigate the impact of digital social responsibility (DSR) on customer trust and brand equity in the context of social commerce. A total of 324 respondents who have experienced in shopping through social commerce participated in this study through an online survey. Design/Methodology/Approach: Structural equation modeling (SEM) was used to test the empirical data derived from surveys with the proposed hypotheses. Findings: The results showed that digital social respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…For example, in their study with South Korean consumers, Park et al (2014) verified that CSR initiatives of a company were positively related to all three dimensions of trusting beliefs. Consistent with this finding, a study by Puwirat and Tripopsakul (2019) found that corporate social responsibility significantly and positively predicted consumer trust in the domain of social commerce.…”
Section: Mediating Role Of Trusting Beliefsmentioning
confidence: 54%
“…For example, in their study with South Korean consumers, Park et al (2014) verified that CSR initiatives of a company were positively related to all three dimensions of trusting beliefs. Consistent with this finding, a study by Puwirat and Tripopsakul (2019) found that corporate social responsibility significantly and positively predicted consumer trust in the domain of social commerce.…”
Section: Mediating Role Of Trusting Beliefsmentioning
confidence: 54%
“…Furthermore, a highly significant p-value(<0.001) was obtained from Bartlett's test of sphericity, suggesting a suitable factor analysis and a strong correlation between the variables. (Puwirat & Tripopsakul, 2019). From Table no 4:We can see that all 17 investment problem items are considered for further analysis because they all have a factor loading above 0.05 (Table no.4).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…DSR programs of an organization attract their customers in various ways. When customers have the opportunity to observe DSR initiatives undertaken by the firm, they are able to participate in DSR activities through dialogs using social media [40]. Given easy access and participation in the DSR programs, customers feel that the business organization is performing according to their perceptions, and they are more likely to become attached to these firms [11].…”
Section: Dsr and Customer Engagement With Dsrmentioning
confidence: 99%
“…Customer engagement with DSR also provides an opportunity for the firm to develop those programs that are associated with the demands of relevant customers [41]. Customer engagement with DSR has attained valuable attention of researchers in the current decade, being considered as the most important and critical factor for the improvement of the overall CSR performance of an organization [40]. In the current study, we argued that, when organizations develop their social responsibilities initiatives according to the demands of stakeholders, these CSR initiatives boost the trust and confidence of stakeholders, which enhances the CSR performance of these organizations.…”
Section: Customer Engagement With Dsr and Csr Performancementioning
confidence: 99%
See 1 more Smart Citation